Bio-oil Production via Catalytic Pyrolysis Process of Chlorella vulgaris Microalgae - ติระพันธ์อำไพ ชาญดนัย; เพชรวโรทัย วรศักดิ์; ภู่สันติ นีรนุช (Progress in Applied Science and Technology, 2017)
In this research, pyrolysis process of Chlorella vulgaris microalgae was studied by a fixed bed reactor. The effect of temperature (400, 500 and 600ºC) and Na2CO3 catalyst/biomass ratio (0, 5, 10 and 20 wt.%) on yields of liquid, solid and gaseous products were investigated. In addition, the influence of catalyst Na2CO3 on chemical compositions of bio-oil produced from pyrolysis was analyzed by gas chromatography/mass spectrometry (GC/MS. Thermogravimetric analysis (TGA) data were very useful to understand thermal behavior and kinetic parameter of pyrolysis process with and without catalyst. As a result, the pyrolysis temperature at 500ºC showed the maximum bio-oil yield of 15.81 wt.% in the absence of Na2CO3. In the presence of Na2CO3 and also the increase of Na2CO3 content, bio-oil yield decreased about 5-6 wt.%. However, the quality of bio-oil obtained from catalytic pyrolysis was enhanced because of the increased aliphatic and aromatic hydrocarbons significantly and decreased acid compounds. The activation energy of catalytic pyrolysis of Chlorella vulgaris was reduced 87.42 kJ/mol compared with the pyrolysis without Na2CO3.